Discovering personality types and diversity based on software team roles - Gilal, Abdul Rehman; Omar, Mazni; Mohd Sharif, Kamal Imran (2013)
Human aspects in software engineering play key role in composing effective team members. However, to date there is no general consensus on the effective personality types and diversity based on team roles.Thus, this paper aims to discover relationships between personality types and diversity based on two software team roles–team leader and programmer.A rule-based approach by using rough set technique was used to discover patterns of the data selected.The results revealed that extrovert personality type is dominant for both software team roles for effective team.The results of this study provide useful rules for decision makers to understand and get insight into selecting effective team members that lead to producing high quality software.